Memory traces: analyzing sacred space at five Mesoamerican sites - Kristan-Graham, Cynthia, editor; Amrhein, Laura M., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2015)
Art historians and archaeologists from the US and Mexico come together to examine the nature of sacred space in Mesoamerica. Contributors explore the process of defining sacred space; how modern Western definitions differ from ancient Mesoamerica; how sacred spaces were conceived and used physically and symbolically; and what theoretical approaches are useful for art historians and archaeologists.--Provided by publisher.
Introduction: Sacred spaces as subject and study in the Mesoamerican landscape / Keith M. Prufer -- Passing through the center: the architectural and social contexts of Teotihuacan painting / Patricia J. Sarro and Matthew H. Robb -- Where rulers are made: spaces of political legitimacy at Tula and el Tajin / Rex Koontz -- Building memories at Tula: sacred landscapes and architectural veneration / Cynthia Kristan-Graham -- The House of the Phalli and the constitution of sacred space through gender performances at Chichen Itza / Laura M. Amrhein and Matthew G. Looper -- Establishing and translating Maya spaces at Tonina and Ocosingo: how indigenous portraits were moved, mutilated, and made Christian in New Spain / Linnea Wren, Travis Nygard, and Kaylee Spencer -- Conclusion: Space, place, ritual, and identity in ancient Mesoamerica / Nicholas P. Dunning and Eric Weaver.
Keywords: Excavations (Archaeology) -- Mexico; Excavations (Archaeology) -- Central America; Indian art -- Mexico; Indian art -- Central America; Sacred space -- Mexico; Sacred space -- Central America; Indians of Mexico -- Antiquities; Indians of Central America -- Antiquities; Mexico -- Antiquities; Central America -- Antiquities